PENGGALIAN PUTUSAN HAKIM: PENERAPAN UNSUR MEMPERKAYA DAN/ATAU MENGUNTUNGKAN DALAM UNDANG-UNDANG TINDAK PIDANA KORUPSI DIKAITKAN DENGAN PUTUSAN PEMIDANAAN TINDAK PIDANA KORUPSI - ANTO WIDI NUGROHO (Muhammadiyah University Press, 2015)
The judge decision in criminal case of corruption is practically happen by disparity case. Therefore, the problem of punishment is not only important for judge and the process of criminal justice, but also the law process entirely, especially in the term of law construction. This research is normative research so the data collecting is done through literary study and qualitative analysis. The result of this research shows that: 1) The regulation of corruption case eradication, there is no explanation include an explanation about element of enrichtment or advantageous but, there is law opinion can be parameter of “enrichment” element in corruption case namely how much the national detriment which has been abused by suspect act. 2) The limitation of national detriment based on the court decision in Sukabumi No. 31/Pid.B/2008/PN.Smi is one hundred million rupiah to make easy the category of enrichment. 3) The implementation of enrichtment and advantageous element by judge in the future is the threat given in the form of incompetence to do in law.